How difficult it is to be God : Shining Path's politics of war in Peru, 1980-1999 - Degregori, Carlos Iván (Critical human rights., 2012)
The revolutionary war launched by Shining Path, a Maoist insurgency, was the most violent upheaval in modern Peru's history, claiming some 70,000 lives in the 1980s and 1990s and drawing widespread international attention. Yet for many observers, Shining Path's initial successes were a mystery. What explained its cult-like appeal, and what actually happened inside the Andean communities at war? In this book, the author - a leading expert on Shining Path and the intellectual architect for Peru's highly regarded Truth and Reconciliation Commission - elucidates the movement's dynamics. An anthropologist who witnessed Shining Path's recruitment of militants in the 1970s, the author grounds his findings in deep research and fieldwork. He explains not only the ideology and culture of revolution among the insurgents, but also their capacity to extend their influence to university youths, indigenous communities, and competing social and political movements. Making this book available to English-language readers for the first time, this translation includes an introduction by the editor, historian Steve J. Stern, who analyzes the author's achievement, why it matters, and the debates it sparked. For anyone interested in Peru and Latin America's age of "dirty war," or in the comparative study of revolutions, Maoism, and human rights, this book will provide arresting insights. -- Publisher's website